MULTIPLE MYELOMA: MENGENALI AWITAN HINGGA PROGNOSIS - Amira Fathin Nabila Yusuf; Mohammad Rizki (Jurnal Medika Hutama, 2023)
Monoclonal neoplasm or plasma cell malignancy is a disease that develops from B cells. One example of a monoclonal neoplasm is multiple myeloma. Multiple Myeloma (MM) is a malignancy that occurs in plasma cells obtained from a single clone. This disease is characterized by the discovery of damage to the skeleton, kidney failure, hypercalcemia, and anemia. The etiology of this disease is still not known with certainty, but several hypotheses have been developed between the influence of environmental factors and cytogenetic abnormalities and oncogenes. MM can be enforced based on the results of anamnesis, physical examination and supporting examinations. The criteria used are the International Myeloma Working Group (IMWG). The principles in the management of MM are systemic therapy to control the progress of MM and supportive therapy. The prognosis of this disease depends on the speed and accuracy of disease identification and the management given.